Who takes care of who takes care? Maternal grief faced with the diagnosis of her son’s autism - Araújo, Joice Natielem Andrade de; Oliveira, Karla Henrique de; Ferraz, Jovana Henrique Cecilio (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No 77 (2024): Publicação Contínua, 2024)
Caring for those who care means considering the situation of mothers who face grief when faced with a child's diagnosis of autism. Grief is not restricted only to death, but to moments of frustration due to situations experienced. Therefore, the objective of this research is to reflect on how this grief can directly affect the mother of an autistic person and what assistance, psychological and emotional care she needs in the face of the diagnosis. This research is relevant because it brings a redirection to the person of the mother, which is often left aside, so in psychology it is important to not only look at the autistic person and redirect the look to the mother. The formation of support networks, such as therapeutic circles aimed at mothers, aims to provide help in dealing with everyday challenges. In view of the content discussed here, we see that the complexity of maternal experiences facing their autistic child is unique, singular and subjective, and it is not possible to accurately explain the depth of this mother's feelings.